Leave no one behind: response to new evidence and guidelines for the management of cryptococcal meningitis in low-income and middle-income countries. Issue 4 (April 2019) - Loyse, Angela; Burry, Jessica; Cohn, Jennifer; Ford, Nathan; Chiller, Tom; Ribeiro, Isabela; Koulla-Shiro, Sinata; Mghamba, Janneth; Ramadhani, Angela; Nyirenda, Rose; Aliyu, Sani H; Wilson, Douglas; et al.
Summary: In 2018, WHO issued guidelines for the diagnosis, prevention, and management of HIV-related cryptococcal disease. Two strategies are recommended to reduce the high mortality associated with HIV-related cryptococcal meningitis in low-income and middle-income countries (LMICs): optimised combination therapies for confirmed meningitis cases and cryptococcal antigen screening programmes for ambulatory people living with HIV who access care. WHO's preferred therapy for the treatment of HIV-related cryptococcal meningitis in LMICs is 1 week of amphotericin B plus flucytosine, and the alternative therapy is 2 weeks of fluconazole plus flucytosine. In the ACTA trial, 1-week (short course) amphotericin B plus flucytosine resulted in a 10-week mortality of 24% (95% CI −16 to 32) and 2 weeks of fluconazole and flucytosine resulted in a 10-week mortality of 35% (95% CI −29 to 41). However, with widely used fluconazole monotherapy, mortality because of HIV-related cryptococcal meningitis is approximately 70% in many African LMIC settings. Therefore, the potential to transform the management of HIV-related cryptococcal meningitis in resource-limited settings is substantial. Sustainable access to essential medicines, including flucytosine and amphotericin B, in LMICs is paramount and the focus of this Personal View.